2004
DOI: 10.1023/b:qure.0000021312.37592.4f
|View full text |Cite
|
Sign up to set email alerts
|

Toward a model of quality of life for family caregivers of stroke survivors

Abstract: The important role of family caregivers in maintaining their disabled and elderly members in the community is becoming increasingly recognized. Caregiver research, for the most part, has explored burden and emotional distress as outcomes of the caregiving experience. Although there is a growing consensus among health-care researchers concerning the importance of quality of life (QoL) as an outcome, there is little research examining QoL of family caregivers. The purpose of this paper, therefore, was to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 44 publications
2
61
0
1
Order By: Relevance
“…In addition, burden and low education were independent predictors of poor HRQoL in caregivers. Negative association between caregiver burden and HRQoL has also been established in western countries [32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, burden and low education were independent predictors of poor HRQoL in caregivers. Negative association between caregiver burden and HRQoL has also been established in western countries [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Some follow-up studies showed that caregiver’s depression and lack of family support may be additional determinants of caregiver burden [37]. The HRQoL, particularly mental health, of primary caregivers appears to decrease over time [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Although quality of life has been an important key concept in research and clinical services, there is still no agreement on what quality of life is and how it should be measured. [64][65][66] Discussion in the literature about (social) participation might mirror the whole conceptual development of the perceived quality of life concept.…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Reviewing the existing literature on stroke caregivers, the authors criticize the scarcity of studies focusing upon physical aspects of health and QoL (quality of life) as well as the lack of longitudinal designs [5, 24, 25]. We know little about how much stroke affects these variables in close relatives.…”
Section: Introductionmentioning
confidence: 99%